Aprroaches to reducing the cardiovascular risk in the late periods of ischemic stroke - A. V. Fonyakin; L. A. Geraskina; V. A. Shandalin (Неврология, нейропсихиатрия, психосоматика, 2010)
Basic antihypertensive, antithrombotic, and antihyperlipidemic therapies form the basis for the prevention of cardiovascular events after ischemic stroke (IS). It is necessary, if indicated, to perform reparative operations on the brachiocephalic arteries. A package of measures to improve the prognosis of a late poststroke period should include the timely detection and adequate therapy of cardiac pathology and the consideration of the predictors of its increased risk. A prospective follow-up of 133 patients with prior IS was conducted to study the prognostic factors of cardiac events in the late poststroke period. During the follow-up, 12 (9%) patients experienced cardiac events, 5 of them died. The outpatient basic treatment of these patients was inadequate. The predictors of poor cardiac prognosis were elderly and senile age, the presence of coronary heart disease, paroxysmal atrial fibrillation, life-threatening ventricular arrhythmias, and reduced heart rhythm variability.